PENGARUH PERSEPSI SISWA TENTANG KETERAMPILAN DASAR MENGAJAR GURU, KEBIASAAN BELAJAR DAN MINAT BELAJAR AKUNTANSI TERHADAP PRESTASI BELAJAR AKUNTANSI - Suningrum Warastuti; Rusno Rusno; Udik Yudiono (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2017)
This study uses the Explanatory Research method, which is a study that explains every relationship between research variables and then tests the hypotheses that have been formulated. The issues raised in this study are about the influence of students' perceptions of basic teaching skills of teachers, study habits and accounting learning interests on accounting achievement of students in the accounting expertise program at SMK NU Bululawang. The results of the study are that there is a significant influence between students' perceptions of the basic teaching skills of teachers, study habits and accounting interest in learning achievement both simultaneously and partially